IMPROVING THE MECHANISMS FOR THE DEVELOPMENT OF THE SOCIAL SERVICE DELIVERY SYSTEM - Shonazarov F.Sh. (The Conference Hub, 2025)
The article examines the organizational and economic mechanisms for developing the social service delivery system in Uzbekistan and explores practical directions for their improvement. Special attention is given to the modernization of social protection through digital technologies and innovative management tools. The study highlights the growing importance of human-centered and inclusive approaches in enhancing the quality of life and ensuring social justice. It also analyzes the role of local governance institutions in expanding access to services and strengthening public trust in the social protection system.
Keywords: social services, social protection, management mechanism, digital transformation, innovation, mahalla (community) institution, human capital.